HUBUNGAN PENGETAHUAN IBU TENTANG 1000 HARI PERTAMA KEHIDUPAN DAN ASUPAN MAKAN DENGAN STATUS GIZI BADUTA - Yulita, Yulita; Jairani, Eka Nenni; Lestari, Wanda; Nababan, Agnes Sry Vera (Jurnal Keperawatan Priority, 2023)
Nutritional deficiencies continue to be a public health issue in Indonesia, particularly in Posyandu Lasoni in Hilizoi Village. Inadequate dietary intake has a severe influence on children if it is not balanced; in the short term, it affects brain development and impairs physical growth, while in the long term, it reduces cognitive capacity and immunity. The study aimed to find out the associated mothers' knowledge of the first 1000 days of life and food intake with toddler nutritional status in Posyandu Lasoni, Hilizoi Village, Gido District, Nias Regency. This research was cross-sectional. Mothers with children aged 6 to 24 months were recruited from Posyandu. Chi-square analysis was used to analyze the data. The results showed that there was a relationship between the mother's knowledge about the first 1000 days of life and the nutritional status of children aged 6-24 months with a p-value = 0.010 (p <0.05), and there is a relationship between food intake for children under five and the nutritional status of children aged 6-24 months with a p-value = 0.013 (p <0.05). It was to expand the understanding of Posyandu cadres, health professionals should be provided training relating to the first 1000 days of life, and it is intended that mothers with under-five children would seek more health information and be more diligent in participating in Posyandu events every month.